Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

The impact of mild hypohydration and sex on the cardiovascular responses to progressive lower-body negative pressure - Megan Hunt; Jenna C. McCrone; Christopher Pignanelli; Monica M. Grigore; Katrin Turetskiy; Gavin C. Lydiate; Alexa A. Robertson; Regan E. J. Parris; Ella M. Bisset-Cavallin; Connor Wideman; Philip J. Millar; Jamie F. Burr; et al. (European Journal of Applied Physiology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Air quality at mass gatherings: assessing ventilation and occupancy in marquees to evaluate airborne infection risk during the COVID-19 pandemic - Ben M. Roberts; Filipa Adzic; Ailsa Hamilton-Smith; Christopher Iddon; Oliver Wild; Malcolm Cook; Steve Gwynne; Aoife Hunt; Liora Malki-Epshtein (Building and Environment, 2026)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Organic alkalinity distributions, characteristics, and application to carbonate system calculations in estuarine and coastal systems - Christopher W. Hunt; Joseph E. Salisbury; Xuewu Liu; Robert H. Byrne (Limnology and Oceanography, 2025)
The capacity of aquatic systems to buffer acidification depends on the sum contributions of various chemical species to total alkalinity (TA). Major TA contributors are inorganic, with carbonate and bicarbonate considered the most important. However, growing evidence shows that many rivers, estuaries, and coastal waters contain dissolved organic molecules with charge sites that create organic alkalinity (OrgAlk). This study describes the first comparison of (1) OrgAlk distributions and (2) acid–base properties in contrasting estuary‐plume systems: the Pleasant (Maine, USA) and the St. John (New Brunswick, CA). The substantial concentrations of OrgAlk in each estuary were sometimes not conservative with salinity and typically associated with very low pH. Two approaches to OrgAlk measurement showed consistent differences, indicating acid–base characteristics inconsistent with the TA definition. The OrgAlk fraction of TA ranged from 78% at low salinity to less than 0.4% in the coastal ocean endmember. Modeling of titration data identified three groups of organic charge sites, with mean acid–base dissociation constants (pK a ) of 4.2 (± 0.5), 5.9 (± 0.7) and 8.5 (± 0.2). These represented 21% (± 9%), 8% (± 5%), and 71% (± 11%) of titrated organic charge groups. Including OrgAlk, pK a , and titrated organic charge groups in carbonate system calculations improved estimates of pH. However, low and medium salinity, organic‐rich samples demonstrated persistent offsets in calculated pH, even using dissolved inorganic carbon and CO 2 partial pressure as inputs. These offsets show the ongoing challenge of carbonate system intercomparisons in organic rich systems whereby new techniques and further investigations are needed to fully account for OrgAlk in TA titrations.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Quantifying sedimentary ’blue carbon’ in relation to canopy cover in the seagrass meadows of Turneffe Atoll, Belize - Stacey L. Felgate; Richard Sanders; Valdemar Andrade; Christopher D. G. Barry; Hannah Brittain; Stephen Carpenter; Abel Carrias; Eliceo Cobb; Chris D. Evans; James Hunt; Anna Lichtschlag; Daniel J. Mayor; et al. (Frontiers in Marine Science, 2024)
Introduction Seagrass sediments are important ‘blue carbon’ reservoirs which store climatically significant quantities of organic carbon (C org ) at the global scale. Seagrass meadows that overly these sediments also provide a range of critical ecosystem services including shoreline stabilization, storm surge protection, and fisheries nursery grounds. However, the controls over accumulation and the sources of organic C to these sediments beds are highly variable and poorly understood with the relative importance of hydrodynamic setting, species composition and canopy density being unclear. Methods Here we address these questions using the first observation-based estimates of C org stocks and provenance on Turneffe Atoll, Belize, made via remotely-sensed habitat extent, local C org data and isotopic data. Sedimentary C org was highest in sediments underlying the most sheltered meadows and decreased with increasing exposure to wind and wave energy with the seagrass meadows in the central lagoon containing an extensive deposit of mangrove derived organic carbon, stabilized and protected by the overlying seagrass meadow. Results The influence of species composition appeared weak with the ubiquitous species T. testudinum occurring across a wide range of hydrodynamic regimes ranging from the most sheltered to the most energetic and being associated with a wide range of sedimentary organic C concentrations. Importantly from the perspective of remote sensing, org C concentrations were unrelated to canopy density. We hypothesize that this decoupling of organic C concentration from seagrass canopy cover reflects a much longer timescale for carbon storage in the sediments than the lifespan of the seagrass plants themselves and/or a substantial non seagrass derived organic C burden in seagrass sediments. Overall, we conservatively estimate that the top 30cm of sediments underlying the seagrass meadows overlying carbonate sediments on the atoll exterior store 0.58 x 10 6 Mg C org , most of which is seagrass-derived, whilst the sediments underlying the meadows within the central lagoon store an additional 1.28 x 10 6 Mg C org . When the maximum possible extent of seagrass is considered, this estimate increases to 3.54 x 10 6 Mg C org. Substantial C org stocks extending >1m depth were observed across all sites, and so these inventories are considered conservative. Discussion A preliminary ‘cost of loss’ for sedimentary C org in the top 30 cm of Turneffe Atoll’s seagrass meadows, based on a carbon trading value of €60 tCO 2 (eq), is estimated at €42 million for the outer atoll, increasing to €136 million when the mangrove-derived sediments of the central atoll are considered and €260 million when turbid areas are assumed to contain seagrass.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Initial Mild Traumatic Brain Injury Characteristics and Recovery Patterns Among Females Across the United States Military Service Academies: A Report from the NCAA-DoD CARE Consortium - Landon B. Lempke; Elsa Ermer; Adrian J. Boltz; Jaclyn Caccese; Thomas A. Buckley; Kenneth L. Cameron; Sara P. D. Chrisman; Christopher D’Lauro; James T. Eckner; Carrie Esopenko; Tamerah N. Hunt; Divya Jain; et al. (Annals of Biomedical Engineering, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Periodicities observed in the solar and geomagnetic indexes and in SABER thermospheric infrared power measurements - Nabil Nowak; Martin G. Mlynczak; Linda Hunt; B. Thomas Marshall; Christopher J. Mertens (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Unintended CRISPR-Cas9 editing outcomes: a review of the detection and prevalence of structural variants generated by gene-editing in human cells - John Murray Topp Hunt; Christopher Allan Samson; Alex du Rand; Hilary M. Sheppard (Human Genetics, 2023)
Genome editing using the clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated protein (Cas) gene-editing system (CRISPR-Cas) is a valuable tool for fundamental and applied research applications. Significant improvements in editing efficacy have advanced genome editing strategies into phase 3 human clinical trials. However, recent studies suggest that our understanding of editing outcomes has lagged behind the developments made in generating the edits themselves. While many researchers have analyzed on- and off-target events through the lens of small insertions or deletions at predicted sites, screens for larger structural variants (SVs) and chromosomal abnormalities are not routinely performed. Full and comprehensive validation of on- and off-target effects is required to ensure reproducibility and to accurately assess the safety of future editing applications. Here we review SVs associated with CRISPR-editing in cells of human origin and highlight the methods used to detect and avoid them.

Rapid changes in coastal ocean microbiomes uncoupled with shifts in environmental variables - Jessica L. Gronniger; Zhao Wang; Genevieve R. Brandt; Christopher S. Ward; Despina Tsementzi; Han Mu; Junyao Gu; Zackary I. Johnson; Konstantinos T. Konstantinidis; Dana E. Hunt (Environmental Microbiology, 2022)
Summary Disturbances, here defined as events that directly alter microbial community composition, are commonly studied in host‐associated and engineered systems. In spite of global change both altering environmental averages and increasing extreme events, there has been relatively little research into the causes, persistence and population‐level impacts of disturbance in the dynamic coastal ocean. Here, we utilize 3 years of observations from a coastal time series to identify disturbances based on the largest week‐over‐week changes in the microbiome (i.e. identifying disturbance as events that alter the community composition). In general, these microbiome disturbances were not clearly linked to specific environmental factors and responsive taxa largely differed, aside from SAR11, which generally declined. However, several disturbance metagenomes identified increased phage‐associated genes, suggesting that unexplained community shifts might be caused by increased mortality. Furthermore, a category 1 hurricane, the only event that would likely be classified a priori as an environmental disturbance, was not an outlier in microbiome composition, but did enhance a bloom in seasonally abundant phytoplankton. Thus, as extreme environmental changes intensify, assumptions of what constitutes a disturbance should be re‐examined in the context of ecological history and microbiome responses.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Factors associated with changes in exercise behaviors during the COVID-19 pandemic - Caroline Himbert; Cassandra A. Hathaway; Bailee Daniels; Karen Salas; Anjelica Ashworth; Biljana Gigic; Tengda Lin; Richard Viskochil; Anne C. Kirchhoff; Douglas Grossman; Jennifer Ose; Jonathan Tward; et al. (Cancer Causes & Control, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Controls on buffering and coastal acidification in a temperate estuary - Christopher W. Hunt; Joseph E. Salisbury; Douglas Vandemark (Limnology and Oceanography, 2022)
Estuaries may be uniquely susceptible to the combined acidification pressures of atmospherically driven ocean acidification (OA), biologically driven CO 2 inputs from the estuary itself, and terrestrially derived freshwater inputs. This study utilized continuous measurements of total alkalinity (TA) and the partial pressure of carbon dioxide (pCO 2 ) from the mouth of Great Bay, a temperate northeastern U.S. estuary, to examine the potential influences of endmember mixing and biogeochemical transformation upon estuary buffering capacity ( β – H ). Observations were collected hourly over 28 months representing all seasons between May 2016 and December 2019. Results indicated that endmember mixing explained most of the observed variability in TA and dissolved inorganic carbon (DIC), concentrations of which varied strongly with season. For much of the year, mixing dictated the relative proportions of salinity‐normalized TA and DIC as well, but a fall season shift in these proportions indicated that aerobic respiration was observed, which would decrease β – H by decreasing TA and increasing DIC. However, fall was also the season of weakest statistical correspondence between salinity and both TA and DIC, as well as the overall highest salinity, TA and β – H . Potential biogeochemically driven β – H decreases were overshadowed by increased buffering capacity supplied by coastal ocean water. A simple modeling exercise showed that mixing processes controlled most monthly changes in TA and DIC, obscuring impacts from air–sea exchange or metabolic processes. Advective mixing contributions may be as important as biogeochemically driven changes to observe when evaluating local estuarine and coastal OA.

Community Science for Coastal Acidification Monitoring and Research - Parker Randall Gassett; Katie O’Brien-Clayton; Carolina Bastidas; Jennie E. Rheuban; Christopher, W. Hunt; Elizabeth Turner; Matthew Liebman; Emily Silva; Adam, R. Pimenta; Jason. Grear; Jackie Motyka; Daniel McCorkle; et al. (Coastal Management, 2021)

Integrating High-Resolution Coastal Acidification Monitoring Data Across Seven United States Estuaries - Nicholas A. Rosenau; Holly Galavotti; Kimberly K. Yates; Curtis C. Bohlen; Christopher W. Hunt; Matthew Liebman; Cheryl A. Brown; Stephen R. Pacella; John L. Largier; Karina J. Nielsen; Xinping Hu; Melissa R. McCutcheon; et al. (Frontiers in Marine Science, 2021)
Beginning in 2015, the United States Environmental Protection Agency’s (EPA’s) National Estuary Program (NEP) started a collaboration with partners in seven estuaries along the East Coast (Barnegat Bay; Casco Bay), West Coast (Santa Monica Bay; San Francisco Bay; Tillamook Bay), and the Gulf of Mexico (GOM) Coast (Tampa Bay; Mission-Aransas Estuary) of the United States to expand the use of autonomous monitoring of partial pressure of carbon dioxide ( p CO 2 ) and pH. Analysis of high-frequency (hourly to sub-hourly) coastal acidification data including p CO 2 , pH, temperature, salinity, and dissolved oxygen (DO) indicate that the sensors effectively captured key parameter measurements under challenging environmental conditions, allowing for an initial characterization of daily to seasonal trends in carbonate chemistry across a range of estuarine settings. Multi-year monitoring showed that across all water bodies temperature and p CO 2 covaried, suggesting that p CO 2 variability was governed, in part, by seasonal temperature changes with average p CO 2 being lower in cooler, winter months and higher in warmer, summer months. Furthermore, the timing of seasonal shifts towards increasing (or decreasing) p CO 2 varied by location and appears to be related to regional climate conditions. Specifically, p CO 2 increases began earlier in the year in warmer water, lower latitude water bodies in the GOM (Tampa Bay; Mission-Aransas Estuary) as compared with cooler water, higher latitude water bodies in the northeast (Barnegat Bay; Casco Bay), and upwelling-influenced West Coast water bodies (Tillamook Bay; Santa Monica Bay; San Francisco Bay). Results suggest that both thermal and non-thermal influences are important drivers of p CO 2 in Tampa Bay and Mission-Aransas Estuary. Conversely, non-thermal processes, most notably the biogeochemical structure of coastal upwelling, appear to be largely responsible for the observed p CO 2 values in West Coast water bodies. The co-occurrence of high salinity, high p CO 2 , low DO, and low temperature water in Santa Monica Bay and San Francisco Bay characterize the coastal upwelling paradigm that is also evident in Tillamook Bay when upwelling dominates freshwater runoff and local processes. These data demonstrate that high-quality carbonate chemistry observations can be recorded from estuarine environments using autonomous sensors originally designed for open-ocean settings.

EATS: a life cycle-based decision support tool for local authorities and school caterers - Valeria De Laurentiis; Dexter V. L. Hunt; Susan E. Lee; Christopher D. F. Rogers (The International Journal of Life Cycle Assessment, 2019)

Bonefish in South Florida: status, threats and research needs - Jacob W. Brownscombe; Andy J. Danylchuk; Aaron J. Adams; Brooke Black; Ross Boucek; Michael Power; Jennifer S. Rehage; Rolando O. Santos; Russ W. Fisher; Bill Horn; Christopher R. Haak; Sean Morton; et al. (Environmental Biology of Fishes, 2019)

Comparing Measures of Estuarine Ecosystem Production in a Temperate New England Estuary - Autumn Oczkowski; Christopher W. Hunt; Kenneth Miller; Candace Oviatt; Scott Nixon; Leslie Smith (Estuaries and Coasts, 2016)

Selective feeding by the giant barrel sponge enhances foraging efficiency - Steven E. McMurray; Zackary I. Johnson; Dana E. Hunt; Joseph R. Pawlik; Christopher M. Finelli (Limnology and Oceanography, 2016)
Foraging theory predicts the evolution of feeding behaviors that increase consumer fitness. Sponges were among the earliest metazoans on earth and developed a unique filter‐feeding mechanism that does not rely on a nervous system. Once thought indiscriminate, sponges are now known to selectively consume picoplankton, but it is unclear whether this confers any benefit. Additionally, sponges consume dissolved organic carbon (DOC) and detritus, but relative preferences for these resources are unknown. We quantified suspension feeding by the giant barrel sponge Xestospongia muta on Conch Reef, Florida, to examine relationships between diet choice, food resource availability, and foraging efficiency. Sponges consistently preferred cyanobacteria over other picoplankton, which were preferred over detritus and DOC; nevertheless, the sponge diet was mostly DOC (∼70%) and detritus (∼20%). Consistent with foraging theory, less‐preferred foods were discriminated against when relatively scarce, but were increasingly accepted as they became relatively more abundant. Food uptake was limited, likely by post‐capture constraints, yet selective foraging enabled sponges to increase nutritional gains.

GPCR structure, function, drug discovery and crystallography: report from Academia-Industry International Conference (UK Royal Society) Chicheley Hall, 1–2 September 2014 - Alexander Heifetz; Gebhard F. X. Schertler; Roland Seifert; Christopher G. Tate; Patrick M. Sexton; Vsevolod V. Gurevich; Daniel Fourmy; Vadim Cherezov; Fiona H. Marshall; R. Ian Storer; Isabel Moraes; Irina G. Tikhonova; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Thermally adaptive tradeoffs in closely related marine bacterial strains - Cheuk‐Man Yung; Marissa K. Vereen; Amy Herbert; Katherine M. Davis; Jiayu Yang; Agata Kantorowska; Christopher S. Ward; Jennifer J. Wernegreen; Zackary I. Johnson; Dana E. Hunt (Environmental Microbiology, 2015)
Summary Time series studies have shown that some bacterial taxa occur only at specific times of the year while others are ubiquitous in spite of seasonal shifts in environmental variables. Here, we ask if these ubiquitous clades are generalists that grow over a wide range of environmental conditions, or clusters of strain‐level environmental specialists. To answer this question, vibrio strains isolated at a coastal time series were phylogenetically and physiologically characterized revealing three dominant strategies within the vibrio: mesophiles, psychrophiles and apparently generalist broad thermal range clades. Thermal performance curves from laboratory growth rate experiments help explain field observations of relative abundances: the mesophilic clade grows optimally at temperatures 16°C higher than the psychrophilic clade. Strains in the broad thermal range clade all have similar optimal growth temperatures but also exhibit temperature‐related tradeoffs with faster growth rates for warm temperature strains and broader growth ranges for strains from cool temperatures. Moreover, the mechanisms of thermal adaptation apparently differ based on evolutionary time scales: shifts in the temperature of maximal growth occur between deeply branching clades but thermal performance curve shape changes on shorter time scales. Thus, apparently ubiquitous clades are likely not generalists, but contain subclusters with distinct environmental preferences.

Ocean and Coastal Acidification off New England and Nova Scotia - Dwight Gledhill; Meredith White; Joe Salisbury; Helmuth Thomas; Ivy Misna; Matthew Liebman; Bill Mook; Jason Grear; Allison Candelmo; R. Christopher Chambers; Christopher Gobler; Christopher Hunt; et al. (Oceanography, 2015)

On the Response of pH to Inorganic Nutrient Enrichment in Well-Mixed Coastal Marine Waters - Scott W. Nixon; Autumn J. Oczkowski; Michael E. Q. Pilson; Lindsey Fields; Candace A. Oviatt; Christopher W. Hunt (Estuaries and Coasts, 2015)

CO2 Input Dynamics and Air–Sea Exchange in a Large New England Estuary - Christopher W. Hunt; Joseph E. Salisbury; Douglas Vandemark (Estuaries and Coasts, 2014)

Genetic epidemiology of cardiometabolic risk factors and their clustering patterns in Mexican American children and adolescents: the SAFARI Study - Sharon P. Fowler; Sobha Puppala; Rector Arya; Geetha Chittoor; Vidya S. Farook; Jennifer Schneider; Roy G. Resendez; Ram Prasad Upadhayay; Jane VandeBerg; Kelly J. Hunt; Benjamin Bradshaw; Eugenio Cersosimo; et al. (Human Genetics, 2013)

Two-Dimensional NMR Evidence for Cleavage of Lignin and Xylan Substituents in Wheat Straw Through Hydrothermal Pretreatment and Enzymatic Hydrolysis - Daniel J. Yelle; Prasad Kaparaju; Christopher G. Hunt; Kolby Hirth; Hoon Kim; John Ralph; Claus Felby (BioEnergy Research, 2013)

Spatial mapping of extracellular oxidant production by a white rot basidiomycete on wood reveals details of ligninolytic mechanism - Christopher G. Hunt; Carl J. Houtman; Don C. Jones; Peter Kitin; Premsagar Korripally; Kenneth E. Hammel (Environmental Microbiology, 2013)
Summary Oxidative cleavage of the recalcitrant plant polymer lignin is a crucial step in global carbon cycling, and is accomplished most efficiently by fungi that cause white rot of wood. These basidiomycetes secrete many enzymes and metabolites with proposed ligninolytic roles, and it is not clear whether all of these agents are physiologically important during attack on natural lignocellulosic substrates. One new approach to this problem is to infer properties of ligninolytic oxidants from their spatial distribution relative to the fungus on the lignocellulose. We grew P hanerochaete chrysosporium on wood sections in the presence of oxidant‐sensing beads based on the ratiometric fluorescent dye BODIPY 581/591. The beads, having fixed locations relative to the fungal hyphae, enabled spatial mapping of cumulative extracellular oxidant distributions by confocal fluorescence microscopy. The results showed that oxidation gradients occurred around the hyphae, and data analysis using a mathematical reaction–diffusion model indicated that the dominant oxidant during incipient white rot had a half‐life under 0.1 s. The best available hypothesis is that this oxidant is the cation radical of the secreted P . chrysosporium metabolite veratryl alcohol.

Cuticular hydrocarbons as a basis for chemosensory self‐referencing in crickets: a potentially universal mechanism facilitating polyandry in insects - Carie B. Weddle; Sandra Steiger; Christopher G. Hamaker; Geoffrey D. Ower; Christopher Mitchell; Scott K. Sakaluk; John Hunt (Ecology Letters, 2013)
Females of many species obtain benefits by mating polyandrously, and often prefer novel males over previous mates. However, how do females recognise previous mates, particularly in the face of cognitive constraints? Female crickets appear to have evolved a simple but effective solution: females imbue males with their own cuticular hydrocarbons ( CHC s) at mating and utilise chemosensory self‐referencing to recognise recent mates. Female CHC profiles exhibited significant additive genetic variation, demonstrating that genetically unique chemical cues are available to support chemosensory self‐referencing. CHC profiles of males became more similar to those of females after mating, indicating physical transfer of CHC s between individuals during copulation. Experimental perfuming of males with female CHC s resulted in a female aversion to males bearing chemical cues similar to their own. Chemosensory self‐referencing, therefore, could be a widespread mechanism by which females increase the diversity of their mating partners.

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

Genetic diversity and phylogeography of broomcorn millet ( Panicum miliaceum L.) across Eurasia - HARRIET V. HUNT; MICHAEL G. CAMPANA; MATTHEW C. LAWES; YONG‐JIN PARK; MIM A. BOWER; CHRISTOPHER J. HOWE; MARTIN K. JONES (Molecular Ecology, 2011)

Contrasting Carbon Dioxide Inputs and Exchange in Three Adjacent New England Estuaries - Christopher W. Hunt; Joseph E. Salisbury; Douglas Vandemark; Wade McGillis (Estuaries and Coasts, 2011)

Mapping SNP-anchored genes using high-resolution melting analysis in almond - Shu-Biao Wu; Iraj Tavassolian; Gholamreza Rabiei; Peter Hunt; Michelle Wirthensohn; John P. Gibson; Christopher M. Ford; Margaret Sedgley (Molecular Genetics and Genomics, 2009)

Involvement of reactive oxygen species in the electrochemical inhibition of barnacle ( Amphibalanus amphitrite ) settlement - Rodolfo E. Pérez-Roa; Marc A. Anderson; Dan Rittschof; Christopher G. Hunt; Daniel R. Noguera (Biofouling, 2009)

Replication of long-bone length QTL in the F9-F10 LG,SM advanced intercross - Elizabeth A. Norgard; Joseph P. Jarvis; Charles C. Roseman; Taylor J. Maxwell; Jane P. Kenney-Hunt; Kaitlin E. Samocha; L. Susan Pletscher; Bing Wang; Gloria L. Fawcett; Christopher J. Leatherwood; Jason B. Wolf; James M. Cheverud (Mammalian Genome, 2009)

Fungal hydroquinones contribute to brown rot of wood - Melissa R. Suzuki; Christopher G. Hunt; Carl J. Houtman; Zachary D. Dalebroux; Kenneth E. Hammel (Environmental Microbiology, 2006)
Summary The fungi that cause brown rot of wood initiate lignocellulose breakdown with an extracellular Fenton system in which Fe 2+ and H 2 O 2 react to produce hydroxyl radicals (·OH), which then oxidize and cleave the wood holocellulose. One such fungus, Gloeophyllum trabeum , drives Fenton chemistry on defined media by reducing Fe 3+ and O 2 with two extracellular hydroquinones, 2,5‐dimethoxyhydroquinone (2,5‐DMHQ) and 4,5‐dimethoxycatechol (4,5‐DMC). However, it has never been shown that the hydroquinones contribute to brown rot of wood. We grew G. trabeum on spruce blocks and found that 2,5‐DMHQ and 4,5‐DMC were each present in the aqueous phase at concentrations near 20 μM after 1 week. We determined rate constants for the reactions of 2,5‐DMHQ and 4,5‐DMC with the Fe 3+ ‐oxalate complexes that predominate in wood undergoing brown rot, finding them to be 43 l mol −1 s −1 and 65 l mol −1 s −1 respectively. Using these values, we estimated that the average amount of hydroquinone‐driven ·OH production during the first week of decay was 11.5 μmol g −1 dry weight of wood. Viscometry of the degraded wood holocellulose coupled with computer modelling showed that a number of the same general magnitude, 41.2 μmol oxidations per gram, was required to account for the depolymerization that occurred in the first week. Moreover, the decrease in holocellulose viscosity was correlated with the measured concentrations of hydroquinones. Therefore, hydroquinone‐driven Fenton chemistry is one component of the biodegradative arsenal that G. trabeum expresses on wood.

Spatial and Temporal Patterns of Inorganic Nutrient Concentrations in the Androscoggin and Kennebec Rivers, Maine - Christopher W. Hunt; Theodore Loder; Charles VÖrÖsmarty (Water, Air, & Soil Pollution, 2005)

Growth and persistence of a recent invader Carcinus maenas in estuaries of the northeastern Pacific - Sylvia Behrens Yamada; Brett R. Dumbauld; Alex Kalin; Christopher E. Hunt; Ron Figlar-Barnes; Andrea Randall (Biological Invasions, 2005)

Biotic resistance experienced by an invasive crustacean in a temperate estuary - Christopher E. Hunt; Sylvia Behrens Yamada (Biological Invasions, 2003)

The yeast polyadenylate-binding protein (PAB1) gene acts as a disease lesion mimic gene when expressed in plants - Qingshun Li; Carol Von Lanken; Jianjun Yang; Christopher B. Lawrence; Arthur G. Hunt (Plant Molecular Biology, 2000)